1968
DOI: 10.1071/ar9680639
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition of the Merino sheep and its sequelae. II. The influence of finite periods of arrested growth on the subsequent wool growth, fleece development, and utilization of feed for wool production of lambs

Abstract: Five groups of Merino lambs were subjected to contrasting nutritional regimes during a preparatory period of 400 days. All animals were then restored to a normal diet and during the subsequent 27 months the sequelae to the experimental treatments were measured in terms of wool growth, fleece development, and the utilization of feed for wool production. The most rigorous treatment (growth arrested for 400 days at 15 kg weight) had as its sequel a less dense wool follicle population (adjusted to a standard body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1970
1970
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…This trial is therefore comparable to those of Henderson (1953), Schinckel (1953), Ryder (1955), Wildman (1958Wildman ( , 1965, and Doney and Smith (1964). The imposed effects are much less severe than those reported by Schinckel and Short (1961) and Allden (1968). It is reasonable to assume from the work of many authors (reviewed by Fraser and Short 1960) that all primary follicles are fully developed before birth.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…This trial is therefore comparable to those of Henderson (1953), Schinckel (1953), Ryder (1955), Wildman (1958Wildman ( , 1965, and Doney and Smith (1964). The imposed effects are much less severe than those reported by Schinckel and Short (1961) and Allden (1968). It is reasonable to assume from the work of many authors (reviewed by Fraser and Short 1960) that all primary follicles are fully developed before birth.…”
Section: Discussionmentioning
confidence: 50%
“…Any delay is transient. Because of the capacity of young sheep to undergo long periods of under-nutrition without impairing wool production in later life (Allden 1968), a situation in which permanent changes in the follicle population could be induced would be extremely rare for Romney sheep under New Zealand grazing conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 In addition, they possess the ability to reduce urine and fecal water losses during times of water deprivation. In general, only very young animals are affected.…”
Section: Watermentioning
confidence: 99%
“…Secondly, net efficiency is the gross efficiency of wool production at maintenance, or the genetic potential for wool growth efficiency. Allden (1979) concluded that high wool producers within a flock consume both more feed and utilise this feed more efficienfiy than low wool producers, whereas differences between strains and breeds of sheep reflects differences in feed intake rather than differences in the gross efficiency of conversion of feed to wool. Pritchard (1988) also showed high producing sheep had higher intake of digestible organic matter and were better able to utilise apparenfiy digested protein for wool production than low wool producing sheep.…”
Section: Bi510 Efficiency Of Wool Productionmentioning
confidence: 99%